APLIKASI IC AT89S51 SEBAGAI PENGONTROL KECEPATAN MOTOR DC - -, Mujiman (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Controlling is tool up to can work as according to what expected by consumer. At controlling of speed of motor dc, matter which is most commonly done voltage regulation. Controlling design speed motor dc uses the IC AT89S51 as especial component at network. Govern the input by knob depress, processed at network of IC AT89S51, and output through of IC ULN200x (as driver), with the motor of dc stepper as controlled burden. LED use as indication of speed choice. Result of perception prove that with the arrangement of speed of motor rotation use the network microcontroller compared to a calculation theory of there are smallest error at low rotation.